Geographical Indications and Trademark Conflicts: A Comparative Study of Legal Protection and Judicial Enforcement - Zeyad Tareq Al-Rawe; Khaled Abdelfatah Mohamed Khalil; Sahar Abdelsttar Emam Aly; Abdelraouf Hassan Abouelhadid; Moustafa Aboumandour Mousa Eisa (Nusantara: Journal of Law Studies, 2026)
Geographical indications (GIs) have become an essential component of the international intellectual property regime, protecting products whose quality, reputation, and commercial value are intrinsically linked to their geographical origin. Nevertheless, conflicts between geographical indications and trademarks continue to create legal uncertainty because of divergent national approaches to ownership, priority, coexistence, and enforcement. This study aims to examine the legal relationship between geographical indications and trademarks comparatively, evaluate the effectiveness of judicial enforcement in resolving such conflicts, and develop an integrated legal protection framework to strengthen the economic competitiveness of GI products in international markets. The research adopts a normative legal methodology with a comparative law approach, analysing international legal instruments, including the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and the Geneva Act of the Lisbon Agreement, together with national legislation and landmark judicial decisions from the European Union, the United States, and selected Arab jurisdictions. The findings demonstrate that the effectiveness of GI protection depends not only on substantive legal provisions but also on the consistency of judicial enforcement and the institutional commitment to preserving the distinctiveness of geographical names. Comparative case analysis further reveals that effective judicial protection strengthens market exclusivity, enhances consumer confidence, and improves product competitiveness, whereas inconsistent enforcement facilitates the genericization of geographical names and diminishes the commercial value of geographical indications. The study concludes that balancing trademark rights and protection of geographical indications requires harmonized legal standards, coherent judicial interpretation, and stronger institutional coordination to prevent consumer confusion while safeguarding legitimate commercial interests. This research contributes to the advancement of comparative intellectual property scholarship by proposing an integrated framework for judicial enforcement that enhances legal certainty, promotes fair competition, preserves product authenticity, and supports the sustainable global competitiveness of geographical indication products.